Examination of drought-vulnerability with GIS tools - Németh, Ákos (Acta Agraria Kaposváriensis, 2004)
Beside floods and inland waters, drought was among the natural hazards that caused important problems in the past few years in Hungary. It affected different fields of economy, agriculture, society etc. Dry climatic periods in the past decades have drawn the attention researchers trying to understand the development of droughts. Preparation for drought periods as well as effective mitigation strategies have important economic values due to the multimillion dollars worth of damage that a drought may cause. It is important to study the drought vulnerability of a certain area to be able to develop useful drought vulnerability mitigation strategies. In this work the drought vulnerability of Somogy county in Southwest Hungary (as the study area) has been determined using data sets characterizing soils, land-use, height of groundwater level, geomorphology of the area, and by studying recent (the past few decades) climatic conditions. The primary aim of the study was to determine the key factors that may influence the development of drought conditions. In addition, evaluation of the weight of certain factors that may contribute to drought vulnerability has been carried out. The final outcome of the study was the classification of certain factors and their representation on various thematic maps. These thematic maps were developed using GIS software such as Surfer (by Golden Software Inc.) and ArcView (by ESRI Inc.). Following the presented droughtvulnerability map, a mitigation plan could be prepared for any areas. The map format of drought vulnerability is a powerful and easy-to-understand tool for non-specialist decision-makers (e.g. members of city councils) working in local communities. Using these maps, drought mitigation could be more effective and therefore more economic.
Keywords: drought-vulnerability; GIS; Somogy county